Surface nanocrystallization modified composite copper powder and preparation method and application thereof
By introducing nano-copper particles to the surface of micron-scale copper powder, the problem of insufficient performance of existing copper powder at low temperature sintering is solved, and efficient application in conductive inks and other fields is achieved.
Patent Information
- Application Number
- CN202411610589.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing micron-scale copper powder has poor performance in low-temperature sintering performance, which limits its application in low-temperature sintering fields such as conductive inks and printed circuits.
By introducing nano-copper particles to the surface of micro- or sub-micron copper powder, the surface nano-modified modified composite copper powder is formed by chemical adsorption, heating and decomposition or reduction treatment using copper precursors such as copper carboxylate salts.
It significantly improves the specific surface area and surface activity of copper powder, increases the diffusion channel and driving force during sintering, reduces the sintering temperature, improves the density and conductivity of the sintered body, and is suitable for low-temperature sintering fields.
Smart Images

Figure CN119457043A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and in particular relates to a surface nano-modified composite copper powder and a preparation method and application thereof, such as conductive ink. Background Art
[0002] In the field of metal material processing, copper is widely used in high-tech fields such as electronics and communications due to its excellent electrical and thermal conductivity. However, the existing micron-sized copper powder has poor low-temperature sintering performance, which limits its application in low-temperature sintering fields such as conductive inks, printed circuits, and conductive connections. In the traditional micron-sized copper powder sintering process, the bonding between particles mainly relies on diffusion, and the sintering driving force of micron-sized copper powder is insufficient, resulting in a low density of the sintered body, which in turn affects its electrical conductivity.
[0003] Therefore, it is necessary to provide a new solution to the above technical problems. Summary of the invention
[0004] The object of the present invention is to provide a surface nano-modified composite copper powder and a preparation method and application thereof, which can improve the low-temperature sintering performance of micron- or submicron-sized copper powder and can be applied to conductive inks, printed circuits, conductive connections and other fields.
[0005] To achieve the above purpose, the technical solution provided by the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing a surface nano-modified composite copper powder, which comprises: impregnating or dispersing a micron-sized or submicron-sized copper powder in a copper precursor solution, wherein the copper precursor comprises a carboxylate copper salt; unavoidable trace amounts of Cu(I) / (II)-valent oxides allow empty orbits to exist on the surface of the copper, and the surface of the micron-sized or submicron-sized copper powder is modified with the carboxylate copper precursor by chemical adsorption; and the micron-sized or submicron-sized copper powder modified with the copper precursor is subjected to a heating decomposition or reduction treatment to form nano-copper particles from the copper precursor, thereby obtaining a composite copper powder having nano-copper particles modified on the surface of the micron-sized or submicron-sized copper powder.
[0007] In one or more embodiments, the copper precursor includes at least one of copper formate, copper acetate, and copper citrate.
[0008] In one or more embodiments, the particle size of the nano copper particles is 50 to 200 nm.
[0009] In one or more embodiments, a micron-sized or submicron-sized copper powder modified with a copper precursor is heated and decomposed to form nano copper particles from the copper precursor, comprising: freeze-drying the micron-sized or submicron-sized copper powder modified with a copper precursor and then spreading it in a container; placing the container in a reaction furnace, introducing an inert protective gas, and heating the micron-sized or submicron-sized copper powder modified with a copper precursor at a temperature of 200 to 400° C. for 30 to 90 minutes to thermally decompose the copper precursor to form nano copper particles.
[0010] In one or more embodiments, a micron-sized or submicron-sized copper powder modified with a copper precursor is subjected to a reduction treatment to form nano copper particles from the copper precursor, comprising: freeze-drying the micron-sized or submicron-sized copper powder modified with a copper precursor and then spreading it in a container; placing the container in a reaction furnace, introducing a reducing protective gas, and heating the micron-sized or submicron-sized copper powder modified with a copper precursor at a temperature of 100 to 300° C. for 30 to 90 minutes to reduce the copper precursor to form nano copper particles.
[0011] In one or more embodiments, the preparation method further comprises: modifying a liquid crystal polymer on the surface of the composite copper powder with the surface modified nano-copper particles.
[0012] In one or more embodiments, after the liquid crystal polymer is dissolved in an organic solvent, the composite copper powder and the liquid crystal polymer are mixed by ultrasonic dispersion and then dried to modify the surface of the composite copper powder with the liquid crystal polymer.
[0013] In a second aspect, the present invention provides a composite copper powder, which is prepared by the aforementioned preparation method of the surface nano-modified composite copper powder.
[0014] In a third aspect, the present invention provides a conductive ink comprising the aforementioned composite copper powder and a sintering aid, wherein the sintering aid comprises at least one of tin, zinc and alloys thereof.
[0015] In one or more embodiments, the mass ratio of the composite copper powder to the sintering aid is (10-20):1.
[0016] In a fourth aspect, the present invention provides application of the aforementioned composite copper powder in the field of low temperature sintering.
[0017] Compared with the prior art, the surface nano-modified composite copper powder provided by the present invention, as well as its preparation method and application, significantly improves the specific surface area and surface activity of the powder by introducing nano-copper particles to modify the surface of micron- or submicron-sized copper powder; this modification process effectively increases the diffusion channel and driving force during sintering of the copper powder, reduces the sintering temperature, and improves the density and conductivity of the sintered body, and can be widely used in low-temperature sintering fields such as conductive inks, printed circuits, and conductive connections. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is a flow chart of a method for preparing a surface nano-modified composite copper powder according to an embodiment of the present invention;
[0020] Figure 2 This is a microscopic morphology of the composite copper powder prepared in Example 1 of the present invention;
[0021] Figure 3 This is a microscopic morphology of the composite copper powder prepared in Example 2 of the present invention;
[0022] Figure 4 This is a microscopic morphology of the composite copper powder prepared in Example 3 of the present invention;
[0023] Figure 5 is the XRD pattern of the composite copper powder prepared in Example 1 of the present invention;
[0024] Figure 6 This is a microscopic morphology of the conductive ink prepared using the composite copper powder of Example 4 after sintering in Application Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] It should be noted that, unless otherwise indicated, all numbers used in the specification and claims to represent feature sizes, quantities and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.2, 1.4, 1.55, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0027] The invention is derived from the in-depth study and analysis of the existing copper powder sintering technology, especially the performance limitations of micron-sized copper powder during low-temperature sintering. Copper powder has a wide range of applications in the fields of electronics and communications due to its excellent electrical and thermal conductivity, especially in low-temperature sintering technologies such as conductive inks and printed circuits. However, traditional micron-sized copper powder requires a higher sintering temperature and exhibits obvious limitations during low-temperature sintering, which seriously affect its effect in practical applications.
[0028] By analyzing the existing technology, the inventors found that when the existing micron-sized copper powder is sintered at low temperature, the bonding between particles mainly depends on the diffusion mechanism, and this diffusion depends on a higher sintering temperature. The existing sintering technology is limited by the small specific surface area of copper powder. Under low temperature conditions (less than 400°C), the diffusion rate between micron-sized copper powder particles is low, and the sintering driving force is insufficient, resulting in low density of the sintered body and excessive growth of grains, which ultimately affects the mechanical and electrical properties of the material.
[0029] The inventors tried to use nano copper powder as a sintering aid, and tried to increase the specific surface area and diffusion channel during the sintering process by adding a small amount of nano copper powder to micron-sized copper powder. However, nano powders tend to agglomerate, resulting in uneven dispersion during the sintering process, which in turn affects the overall performance of the sintered body.
[0030] In this context, the present invention proposes a new method for preparing surface nano-modified composite copper powder, which aims to improve the sintering performance of copper powder through surface modification technology. The core technology of the present invention is to introduce nano-copper particles to modify the surface of micron- or submicron-sized copper powder, thereby significantly improving the specific surface area and surface activity of the powder. By selecting a suitable copper precursor (such as copper carboxylate), the copper precursor is evenly distributed on the surface of the copper powder by chemical adsorption, and then the precursor is converted into nano-copper particles by heating decomposition or reduction. This modification process effectively increases the diffusion channel and driving force during the sintering of copper powder, and improves the density of the sintered body.
[0031] The idea of implementing this technology further utilizes the high surface energy of nanoparticles, combined with the modification effect of the material surface, to optimize the bonding between copper powder particles during the sintering process. The presence of nanoparticles effectively inhibits the movement of grain interfaces and prevents excessive grain growth by forming a "nano-bridge" effect between particles. Through this innovative idea, the present invention not only solves the problems of low density and poor mechanical properties of existing copper powder sintered bodies, but also effectively avoids excessive grain growth and improves the microstructure of the sintered body.
[0032] Please refer to Figure 1 FIG. 1 is a flow chart of a method for preparing a surface nano-modified composite copper powder according to an embodiment of the present invention. The method for preparing a surface nano-modified composite copper powder specifically comprises the following steps:
[0033] S101: impregnating or dispersing micron-sized or submicron-sized copper powder in a copper precursor solution, wherein the copper precursor includes copper carboxylate.
[0034] The micron or submicron copper powder is impregnated or dispersed in the copper precursor solution, thus laying the foundation for the subsequent chemical adsorption and thermal decomposition steps. The copper precursor used is a copper carboxylate salt, which is dissolved in a solvent to form a uniform solution. For copper formate and copper citrate that cannot be completely dissolved, a roller grinding and dispersion method is used to make them small enough particles that can effectively cover the surface of the copper powder.
[0035] Specifically, the impregnation or dispersion process can be achieved in a variety of ways. For example, the copper powder can be directly immersed in a solution containing a precursor, and then stirring or ultrasonic dispersion can be used to ensure that the copper powder is evenly distributed in the solution to avoid agglomeration. Taking copper acetate as an example, it is dissolved in water or an organic solvent to prepare a solution, and then micron-sized copper powder is added to it. To ensure that the copper powder is fully contacted in the precursor solution, an ultrasonic disperser or mechanical stirring equipment can be used for a certain period of time to ensure that the precursor can be evenly adsorbed on the surface of each copper powder particle.
[0036] Preferably, the copper precursor includes at least one of copper formate, copper acetate and copper citrate.
[0037] Copper formate (Cu(HCOO)2) is a common copper precursor with a low decomposition temperature (below 200°C). Copper formate decomposes under heating conditions to produce copper, carbon dioxide and water, thereby forming stable nano copper particles. This feature makes it an ideal precursor in the preparation method of the present invention, especially in applications where it is desired to form uniformly distributed nano copper particles at a lower temperature. Due to its relatively low decomposition temperature, the use of copper formate as a precursor can effectively reduce energy consumption and reduce the risk of oxidation of copper powder during the decomposition process.
[0038] Copper acetate (Cu(CH3COO)2) is also a commonly used copper precursor. Its decomposition temperature is slightly higher than that of copper formate (about 200-250°C), but it has good solubility and decomposition characteristics. During the heating process, copper acetate releases volatile products such as carbon dioxide and water, and generates nano-copper particles. The advantage of copper acetate is that it has good chemical stability and can be dissolved in a variety of solvents, which is suitable for different process conditions. In addition, the particle size of copper particles generated after the decomposition of copper acetate can be precisely controlled by adjusting the temperature and reaction time, so it has advantages in applications that require larger particle sizes.
[0039] Copper citrate (Cu3(C6H5O7)2) has higher chemical complexity than the first two, and its decomposition temperature is also higher (usually above 250°C). The molecular structure of copper citrate is larger, and it can provide a variety of coordination sites for chemical adsorption with the copper powder surface. Therefore, the nano-copper particles formed after decomposition often have better dispersibility. Since copper citrate has stronger coordination ability, it can not only generate nano-copper particles during the decomposition process, but also effectively inhibit the agglomeration of particles, ensuring the uniformity of the final composite copper powder. In addition, the presence of citrate helps to provide a certain reducing environment during the reaction process and reduce the oxidation reaction on the surface of the copper powder.
[0040] S102: modifying the surface of micron-sized or submicron-sized copper powder with a copper precursor through chemical adsorption.
[0041] The inevitable Cu(I) / (II) oxides on the surface of pure copper powder make the surface copper have empty orbitals. During the chemical adsorption process, the precursor molecules form a bond with the copper powder surface through coordination bonds, electrostatic effects or van der Waals forces, thereby forming a uniform precursor coating on the copper powder surface.
[0042] In a specific implementation, the copper powder can be dispersed in a copper precursor solution, so that the copper ions or precursor molecules in the precursor solution are adsorbed to the surface of the copper powder through chemical action. For example, copper formate, copper acetate or copper citrate is dissolved in water or an organic solvent as a copper precursor to form a precursor solution, and then the copper powder is added thereto and stirred or ultrasonically treated. Stirring or ultrasonic waves can enhance the dispersibility of the copper powder and ensure that the precursor solution can fully contact the surface of the copper powder. Through the intermolecular force, the precursor molecules gradually cover the surface of the copper powder to form a uniform film.
[0043] In the chemical adsorption process, the intensity of the adsorption process is related to the chemical structure of the precursor and the physicochemical properties of the copper powder surface. Carboxylic acid copper precursors (such as copper formate, copper acetate, and copper citrate) can coordinate with the copper powder surface through carboxyl groups to form stable chemical bonds. In addition, the concentration of the precursor solution and the adsorption time also need to be controlled. Insufficient adsorption will lead to insufficient nano effect and insufficient sintering driving force. Excessive concentration or excessively long adsorption time may lead to local aggregation, affecting the uniformity of nano copper particles during subsequent decomposition. Usually in actual operation, the concentration of the precursor solution is controlled in the range of 40-60%, and ultrasonic treatment is performed for 30-60 minutes to ensure that the precursor is evenly attached to the copper powder surface.
[0044] Through step S102, a uniform precursor layer can be formed on the surface of the copper powder, and this process creates necessary conditions for the subsequent thermal decomposition or reduction step. Through chemical adsorption and electrostatic adsorption, the precursor can be tightly combined with the surface of the copper powder to ensure that it will not fall off or be unevenly distributed during heating. The uniform film generated during the adsorption process can significantly improve the subsequent formation efficiency of nano copper particles and ensure that nano copper particles can be uniformly generated during heating.
[0045] S103: performing heating decomposition or reduction treatment on the micron-sized or submicron-sized copper powder modified with the copper precursor to form nano-sized copper particles from the copper precursor, thereby obtaining a composite copper powder with nano-sized copper particles modified on the surface of the micron-sized or submicron-sized copper powder.
[0046] Step S103 mainly involves heating and decomposing or reducing the micron-sized or submicron-sized copper powder modified with the copper precursor by chemical adsorption, so as to reduce the copper ions in the copper precursor to metallic copper, form uniformly distributed nano-copper particles, and obtain composite copper powder.
[0047] Copper powder modified with a copper precursor can be placed in a temperature-controlled ultrasonic reaction furnace, and the precursor can be decomposed by heating to form nano copper particles. For copper carboxylates such as copper formate or copper acetate, the decomposition temperature is generally between 150 and 400°C, and the specific temperature depends on the type of precursor. Usually, it is carried out under a reducing atmosphere (such as a hydrogen or ammonia decomposition atmosphere) to avoid copper oxidation. When the temperature reaches the decomposition temperature of the precursor, the carboxylate ions decompose to generate gaseous products such as carbon dioxide and water, and the copper ions are reduced to metallic copper, which is deposited on the surface of the copper powder to form nano copper particles. In this process, furnace heating and additional ultrasonic treatment are beneficial to obtain composite copper powder with better dispersibility.
[0048] The reduction treatment is usually carried out at a relatively low temperature (100-300°C) to reduce the copper ions in the copper precursor to metallic copper through a reducing atmosphere (such as hydrogen or ammonia decomposition gas). This method is milder than thermal decomposition and is suitable for temperature-sensitive materials. At the same time, the reducing atmosphere can further prevent copper oxidation. In a reducing environment, when the copper precursor decomposes, the copper ions are reduced to nano-copper particles and attached to the surface of the copper powder.
[0049] In an exemplary embodiment, the particle size of the nano copper particles is 50 to 200 nm. Nano copper particles with a particle size of 50 to 200 nm also help to improve the sintering density and mechanical properties of the material. In the sintering process of traditional micron-sized copper powder, the contact area between larger particles is limited, resulting in insufficient diffusion driving force. By modifying the surface of the copper powder with nano copper particles within this particle size range, the gaps between the copper powders can be filled to form a more uniform microstructure. During the sintering process, these nanoparticles play a "bridging" role, promoting a closer combination of the copper powder particles, thereby improving the overall strength and density of the sintered body.
[0050] In an exemplary embodiment, a micron-sized or submicron-sized copper powder modified with a copper precursor is heated and decomposed to form nano-sized copper particles from the copper precursor, specifically comprising: freeze-drying the micron-sized or submicron-sized copper powder modified with a copper precursor and then spreading it in a container; placing the container in an ultrasonic reactor, introducing an inert protective gas (such as argon), and heating the micron-sized or submicron-sized copper powder modified with a copper precursor at a temperature of 150 to 400° C. for 30 to 90 minutes to thermally decompose the copper precursor to form nano-sized copper particles.
[0051] Before thermal decomposition or reduction treatment, the copper powder modified with the copper precursor can be freeze-dried. The purpose of freeze-drying is to remove the residual solvent in the copper powder, reduce the free and slow growth of the copper precursor in the solution, and cause the aggregation and growth of its own particles, so as to ensure that the precursor can be evenly decomposed during the heating process, and will not cause uneven thermal decomposition or agglomeration due to the residual solvent. In the specific operation, the adsorbed copper powder suspension is placed in a freeze-drying device, the temperature is dropped to below -40°C, the solvent is frozen, and then the solid solvent is directly sublimated out of the system by increasing the vacuum degree. This treatment ensures that the precursor on the surface of the copper powder remains intact and uniform, and the copper powder is not oxidized and still has a high dispersibility.
[0052] In an exemplary embodiment, a micron-sized or submicron-sized copper powder modified with a copper precursor is subjected to a reduction treatment to form nano-copper particles from the copper precursor, specifically comprising: freeze-drying the micron-sized or submicron-sized copper powder modified with a copper precursor and then spreading it in a container; placing the container in a reaction furnace, introducing a reducing protective gas, and heating the micron-sized or submicron-sized copper powder modified with a copper precursor at a temperature of 100 to 300° C. for 30 to 90 minutes to reduce the copper precursor to form nano-copper particles.
[0053] In an exemplary embodiment, the preparation method further comprises: modifying a liquid crystal polymer on the surface of the composite copper powder with the surface modified nano-copper particles.
[0054] The main function of liquid crystal polymers is to provide self-healing function and enhance the mechanical stability of materials, while also preventing defects that may occur during the sintering process. Liquid crystal polymers such as polyarylate liquid crystal polymers (such as Vectra) have good self-healing function. When microcracks or damage occur in the material during the sintering process or when subjected to external forces, liquid crystal polymers can fill these cracks by rearranging their molecular structure to prevent further crack expansion. This can significantly improve the mechanical properties of the sintered body and reduce the formation of internal defects in the material. Secondly, liquid crystal polymers can provide a certain buffering effect during the sintering process, preventing excessive contact or adhesion between copper powder particles and avoiding particle agglomeration.
[0055] Specifically, after the liquid crystal polymer is dissolved in an organic solvent, the composite copper powder and the liquid crystal polymer are mixed by ultrasonic dispersion, and then dried and solidified, so that the liquid crystal polymer is modified on the surface of the composite copper powder.
[0056] Liquid crystal polymers are usually difficult to dissolve in water, so specific organic solvents are required, such as chloroform, dichloromethane, etc. These solvents can effectively dissolve liquid crystal polymers to form a uniform solution, thereby ensuring that the liquid crystal polymer can be evenly attached to the surface of the copper powder during the dispersion process.
[0057] The uniform mixing of composite copper powder and liquid crystal polymer can be achieved by ultrasonic dispersion. The ultrasonic dispersion method disperses the liquid crystal polymer on the surface of copper powder by generating high-frequency vibration, thus avoiding the agglomeration of polymer particles. Ultrasonic dispersion technology uses the cavitation effect in the liquid to decompose the liquid crystal polymer into tiny particles and evenly distribute them. In the specific operation, after the copper powder and liquid crystal polymer solution are mixed, they are treated in an ultrasonic disperser for 30 to 60 minutes to make the liquid crystal polymer evenly attached to the surface of the copper powder particles.
[0058] After dispersion, the copper powder needs to be dried to remove the solvent and ensure that the liquid crystal polymer is evenly attached to the surface of the copper powder particles. Common drying methods include low-temperature evaporation in a vacuum environment or using a rotary evaporator to remove the solvent. The core of this step is to avoid excessive temperature causing the liquid crystal polymer to decompose prematurely or lose its function, so the drying process is usually carried out under mild conditions of 40 to 60°C.
[0059] The liquid crystal polymer is shaped and stably attached to the surface of the copper powder through the curing process. The curing process is usually carried out at a temperature of 100-150°C to ensure that the liquid crystal polymer can maintain its unique molecular arrangement structure and provide functionality during the subsequent sintering process. The purpose of this step is to make the liquid crystal polymer coating have stable mechanical properties and thermal stability, thereby preventing particle agglomeration during the sintering process and improving the strength of the sintered body.
[0060] In the present invention, before the surface of the copper powder is modified with nanoparticles, a copper precursor (such as copper carboxylate) is first evenly distributed on the surface of the copper powder by chemical adsorption technology. The precursor can be stably attached to the surface of the copper powder by chemical adsorption to form a uniform precursor coating. Subsequently, the precursor is heated and decomposed or reduced to generate nano-scale copper particles, which are evenly distributed on the surface of the micron-scale copper powder.
[0061] Compared with traditional micron-sized copper powder, the surface-modified composite copper powder can be sintered at a lower temperature, which is particularly important for low-temperature applications. Conductive inks, printed electronics, and low-temperature conductive pastes usually require lower sintering temperatures. Using this nano-modification technology, composite copper powder can be sintered at a lower temperature of 150 to 300°C, protecting substrates (such as plastics, paper-based materials, etc.) or components that are susceptible to high temperatures and significantly reducing energy consumption.
[0062] In addition, through the modification of nanoparticles, the composite copper powder in the present invention can form a denser microstructure after sintering, reduce porosity, and enhance the bonding strength between particles, thereby improving the conductivity and mechanical strength of the material, which helps to achieve high stability and long life requirements in electronic materials.
[0063] An embodiment of the present invention further provides a composite copper powder, which is prepared by the above-mentioned preparation method.
[0064] In one embodiment of the present invention, a conductive ink is further provided, which includes the composite copper powder obtained by the preparation method and a sintering aid, wherein the sintering aid includes at least one of submicron tin, zinc and their alloys. Tin (Sn), zinc (Zn) and their alloys as sintering aids can provide a liquid phase during the sintering process, promote the close bonding of copper powder particles, and reduce the sintering temperature, and are suitable for the application of conductive ink under low-temperature sintering.
[0065] As low melting point metals, tin and zinc can melt at a lower temperature to form a liquid phase. During the sintering process, the liquid phase can wet and fill the gaps between copper powder particles, increase the contact area between particles, accelerate diffusion and bonding, and promote the formation of densification.
[0066] In conductive inks, tin and zinc can melt at low temperatures to form an instantaneous liquid phase, which helps copper powder particles to be effectively sintered at low temperatures. Solid solution or alloying reactions may also occur between tin, zinc and copper, further improving the mechanical strength and conductivity of the material.
[0067] In an exemplary embodiment, the mass ratio of the composite copper powder to the sintering aid is (10-20): 1. The composite copper powder is the main component in this ratio. As the core conductive material of the conductive ink, the main function of the copper powder is to provide excellent conductivity.
[0068] Too little additive (such as a mass ratio greater than 20:1) may not effectively form a sufficient liquid phase, and the density and conductivity of the sintered body are difficult to achieve the desired effect. Too much additive (such as less than 10:1) may lead to excessive liquid phase, destroy the shape stability of the ink film layer, and affect the conductivity. In addition, the conductivity of these alloys is lower than that of copper, and excessive introduction will reduce the conductivity.
[0069] The composite copper powder provided by the present invention has excellent low-temperature sintering performance and can be widely used in the field of low-temperature sintering, such as conductive ink, printed circuits, conductive connections, etc.
[0070] The present invention will be further described below in conjunction with specific embodiments and comparative examples.
[0071] Example 1
[0072] Weigh 500 g of copper formate, grind it by wet method and disperse it in deionized water to obtain a copper formate solution with a concentration of about 50%; add 500 g of D 50 The water-atomized ultrafine copper powder of 2.5 μm was stirred and mixed evenly, and then freeze-dried to obtain a mixed powder. The mixed powder was spread in a 20 cm × 30 cm × 3 cm stainless steel plate, placed in a heating furnace with ultrasonic vibration, using an ammonia decomposition atmosphere, at 200 ° C, maintained for 60 minutes, and cooled for 60 minutes to obtain a composite copper powder with surface nano-modification.
[0073] Figure 2 This is a microscopic morphology of the composite copper powder obtained in Example 1. The size of the surface modification particles (nano copper particles) of the composite copper powder is 50-200 nm, and the specific surface area of the composite copper powder is 4.78 m 2 / g. Figure 5 This is the XRD pattern of the composite copper powder prepared in Example 1.
[0074] Example 2
[0075] Weigh 600 g of copper acetate and dissolve it in deionized water to obtain a copper acetate solution with a concentration of about 50%; add 500 g of D 50 The water-atomized ultrafine copper powder of 2.5 μm was stirred and mixed evenly, and then freeze-dried to obtain a mixed powder. The mixed powder was spread in a 20 cm × 30 cm × 3 cm stainless steel plate, placed in a heating furnace with ultrasonic vibration, using an ammonia decomposition atmosphere, at 250 ° C, maintained for 60 minutes, and cooled for 60 minutes to obtain a composite copper powder with surface nano-modification.
[0076] Figure 3 This is a microscopic morphology of the composite copper powder obtained in Example 2. The size of the surface modification particles (nano copper particles) of the composite copper powder is 50-200 nm, and the specific surface area of the composite copper powder is 4.86 m 2 / g.
[0077] Example 3
[0078] Weigh 600 g of copper citrate, grind it by wet method and disperse it in deionized water to obtain a copper citrate solution with a concentration of about 50%; add 500 g of D 50 The water-atomized ultrafine copper powder of 2.5 μm was stirred and mixed evenly, and then freeze-dried to obtain a mixed powder. The mixed powder was spread in a 20 cm × 30 cm × 3 cm stainless steel plate, placed in a heating furnace with ultrasonic vibration, using argon as the protective gas, at 250 ° C, kept for 60 minutes, and cooled for 60 minutes to obtain a composite copper powder with surface nano-modification.
[0079] Figure 4 This is a microscopic morphology of the composite copper powder obtained in Example 3. The size of the surface modification particles (nano copper particles) of the composite copper powder is 50-200 nm, and the specific surface area of the composite copper powder is 4.99 m 2 / g.
[0080] Example 4
[0081] Take 20 g of liquid crystal polymer ( FIT50), added to 200 ml of chloroform, and stirred at room temperature for 30 minutes using a magnetic stirrer to ensure that the liquid crystal polymer was dissolved to form a uniform solution.
[0082] 100 g of the composite copper powder prepared in Example 1 was added to the prepared liquid crystal polymer solution, and 1 g of PVP was added as a dispersant to improve the dispersibility of the copper powder. The treatment was performed using an ultrasonic disperser for 60 minutes. The frequency of the ultrasonic wave was set to 40 kHz and the power was set to 200 W to ensure that the copper powder was evenly distributed in the solution and attached to the liquid crystal polymer.
[0083] The treated mixed slurry is used to remove most of the solvent by a rotary evaporator, and then the remaining suspension is placed in a vacuum drying oven and dried at 40° C. for 12 hours until the solvent is completely evaporated to obtain copper powder with a surface modified with a liquid crystal polymer.
[0084] The dried copper powder was evenly spread on a stainless steel plate through a sieve (200 mesh) and placed in an oven for curing. The curing temperature was set at 120°C and the holding time was 1 hour to ensure that the liquid crystal polymer was stably attached to the surface of the copper powder. After the curing treatment was completed, the copper powder was naturally cooled to room temperature to obtain the final composite copper powder modified with liquid crystal polymer.
[0085] Comparative Example 1
[0086] D 50 It is 2.5μm water atomized ultrafine copper powder.
[0087] Comparative Example 2
[0088] Take 20 g of polydimethylsiloxane and add it to 200 ml of n-hexane. Stir it at room temperature for 30 minutes using a magnetic stirrer to form a uniform solution.
[0089] 100 g of the composite copper powder prepared in Example 1 was added to the prepared polydimethylsiloxane solution, and 1 g of PVP was added as a dispersant to improve the dispersibility of the copper powder. The treatment was performed using an ultrasonic disperser for 60 minutes. The frequency of the ultrasonic wave was set to 40 kHz and the power was set to 200 W to ensure that the copper powder was evenly distributed in the solution and attached to the polydimethylsiloxane.
[0090] The treated mixed slurry was used to remove most of the solvent by a rotary evaporator, and then the remaining suspension was placed in a vacuum drying oven and dried at 40° C. for 12 hours until the solvent was completely evaporated to obtain copper powder with the surface modified with polydimethylsiloxane.
[0091] The dried copper powder was evenly spread on a stainless steel plate through a sieve (200 mesh) and placed in an oven for curing. The curing temperature was set to 120°C and the holding time was 1 hour to ensure that polydimethylsiloxane was stably attached to the surface of the copper powder. After the curing treatment was completed, the copper powder was naturally cooled to room temperature to obtain the final composite copper powder modified with polydimethylsiloxane.
[0092] Preparation of conductive ink
[0093] Application Example 1
[0094] The copper powders prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were mixed with a sintering aid (tin powder with a particle size of 300 to 800 nm) respectively, and the mass ratio of the composite copper powder to the sintering aid was 15:1. An appropriate amount of ethanol solvent was added to adjust the viscosity of the ink to make it suitable for printing processes (such as screen printing). At the same time, a dispersant (polyvinyl pyrrolidone, PVP) was added to maintain uniform distribution of the composite copper powder and the sintering aid in the solvent.
[0095] Use a high-speed stirrer or ultrasonic dispersing equipment to fully mix the composite copper powder, sintering aid and solvent so that the aid and copper powder are evenly distributed in the entire ink system.
[0096] Figure 6 This is a microscopic morphology of the conductive ink prepared using the composite copper powder of Example 4 after sintering in Application Example 1 of the present invention.
[0097] Application Example 2
[0098] Compared with Application Example 1, no sintering aid was added in Application Example 2, and other conditions were the same as those in Application Example 1.
[0099] Performance Testing
[0100] (1) Observe whether the conductive inks prepared in Application Example 1 and Application Example 2 are agglomerated;
[0101] (2) The conductive ink prepared from the composite copper powder of Examples 1 to 4 and Comparative Example 1 was screen printed on a substrate to form a circuit, and then cured at 200°C; after the curing was completed, the circuit was observed for cracks and its resistivity was tested. The test results are shown in Table 1:
[0102] Table 1 - Performance test results
[0103]
[0104]
[0105] It can be seen from the performance test results in Table 1 that the low-temperature sintering performance of micron-sized copper powder can be improved by surface-modifying nano-copper particles. Further modification of liquid crystal polymer on the surface of copper powder plays a role of self-healing and anti-oxidation, which can further improve the sintering performance of copper powder. In addition, the addition of sintering aids helps to improve the sintering structure and reduce the generation of cracks.
[0106] Liquid crystal polymers have the ability to rearrange their molecules during high-temperature sintering. When microcracks or pores are generated by heat in the material, the liquid crystal polymer molecules can fill these defects by self-adjusting and rearranging to prevent them from expanding. Therefore, the liquid crystal polymer coating can automatically repair certain microscopic defects during the sintering process and improve the mechanical strength and density of the sintered body.
[0107] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0108] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a surface nano-modified composite copper powder, characterized in that: include: impregnating or dispersing micron-sized or submicron-sized copper powder in a copper precursor solution, wherein the copper precursor includes a copper carboxylate salt; The surface of micron-sized or submicron-sized copper powder is modified with a copper precursor by chemical adsorption; The micron-sized or submicron-sized copper powder modified with a copper precursor is subjected to heating decomposition or reduction treatment to form nano copper particles from the copper precursor, thereby obtaining a composite copper powder with nano copper particles modified on the surface of the micron-sized or submicron-sized copper powder.
2. The method for preparing the surface nano-modified composite copper powder according to claim 1, characterized in that: The copper precursor includes at least one of copper formate, copper acetate and copper citrate.
3. The method for preparing the surface nano-modified composite copper powder according to claim 1, characterized in that: The particle size of the nano copper particles is 50-200 nm.
4. The method for preparing the surface nano-modified composite copper powder according to claim 1, characterized in that: The micron-sized or submicron-sized copper powder modified with a copper precursor is heated and decomposed to form nano copper particles from the copper precursor, including: The micron-sized or submicron-sized copper powder modified with the copper precursor is freeze-dried and then spread in a container; The container is placed in a reaction furnace, an inert protective gas is introduced, and the micron-sized or submicron-sized copper powder modified with a copper precursor is heated at a temperature of 200 to 400° C. for 30 to 90 minutes to thermally decompose the copper precursor to form nano copper particles.
5. The method for preparing the surface nano-modified composite copper powder according to claim 1, characterized in that: The micron-sized or submicron-sized copper powder modified with a copper precursor is subjected to reduction treatment to form nano-copper particles from the copper precursor, including: The micron-sized or submicron-sized copper powder modified with the copper precursor is freeze-dried and then spread in a container; The container is placed in a reaction furnace, a reducing protective gas is introduced, and the micron-sized or submicron-sized copper powder modified with a copper precursor is heated at a temperature of 100 to 300° C. for 30 to 90 minutes to reduce the copper precursor to form nano copper particles.
6. The method for preparing the surface nano-modified composite copper powder according to any one of claims 1 to 5, characterized in that: The preparation method further comprises: The surface of the composite copper powder with nano copper particles modified on the surface is modified with a liquid crystal polymer.
7. The method for preparing the surface nano-modified composite copper powder according to claim 6, characterized in that: After the liquid crystal polymer is dissolved by an organic solvent, the composite copper powder and the liquid crystal polymer are mixed evenly by an ultrasonic dispersion method, and then dried, so that the liquid crystal polymer is modified on the surface of the composite copper powder.
8. A composite copper powder, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. A conductive ink, characterized in that: It comprises the composite copper powder as claimed in claim 8 and a sintering aid, wherein the sintering aid comprises at least one of submicron tin, zinc and alloys thereof; the mass ratio of the composite copper powder to the sintering aid is (10-20):
1.
10. Use of the composite copper powder according to claim 8 in the field of low temperature sintering.